Do wildfire experiences influence views on climate change?. Issue 2 (18th May 2015) - Millar, Joanne Elaine; Boon, Helen; King, David
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – This paper aims to explore the influence of wildfire events on community perceptions of climate change and the risk of future wildfire disasters in southern Australia. Design/methodology/approach – The study was located around Beechworth in northeast Victoria, where wildfires occurred in 2003 and 2009. Semi-structured qualitative interviews and focus group interviews were conducted in 2010, involving 40 people from local businesses, government and property owners. Findings – The authors conclude that people's experiences of recent consecutive wildfire events did not necessarily influence their views on climate change in general or as a causal agent of wildfire events. However, there was general agreement that weather conditions had been extreme in recent times. Some attributed the increase in wildfires to factors other than climate change that were more easily observed. Research limitations/implications – Further research is needed into the relationship between wildfire experiences, climate change views and adaptive behaviours across a wider range of social contexts. Research needs to determine if views and behaviours change over time or with frequency or severity of fires. Practical implications – Understanding the nature of potential wildfires, and being able to prepare and respond to such events, is more important than believing in climate change, as views may not change in response to fire events. Strategies need to focus on supporting people to prepare, respond and recover from wildfires, regardless of their climate change perceptions. Social implications – Paying attention to people's local social context and how it influences their beliefs about climate change will allow sensitive and adaptive strategies to evolve over time. Originality/value – There is limited research into relationships between disaster experiences and perceptions of climate change, particularly the influence of wildfire experiences.